Loss of MINAR2 impairs motor function and causes Parkinson's disease-like symptoms in mice. Issue 1 (21st April 2020) - Ho, Rachel Xi-Yeen; Amraei, Razie; De La Cena, Kyle Oliver Corcino; Sutherland, Evan G; Mortazavi, Farzad; Stein, Thor; Chitalia, Vipul; Rahimi, Nader
Abstract: Parkinson's disease is the second most common human neurodegenerative disease. Motor control impairment represents a key clinical hallmark and primary clinical symptom of the disease, which is further characterized by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta and the accumulation of α-synuclein aggregations. We have identified major intrinsically disordered NOTCH2-associated receptor 2 encoded by KIAA1024L, a previously uncharacterized protein that is highly conserved in humans and other species. In this study, we demonstrate that major intrinsically disordered NOTCH2-associated receptor 2 expression is significantly down-regulated in the frontal lobe brain of patients with Lewy body dementia. Major intrinsically disordered NOTCH2-associated receptor 2 is predominantly expressed in brain tissue and is particularly prominent in the midbrain. Major intrinsically disordered NOTCH2-associated receptor 2 interacts with neurogenic locus notch homologue protein 2 and is localized at the endoplasmic reticulum compartments. We generated major intrinsically disordered NOTCH2-associated receptor 2 knockout mouse and demonstrated that the loss of major intrinsically disordered NOTCH2-associated receptor 2 in mouse results in severe motor deficits such as rigidity and bradykinesia, gait abnormalities, reduced spontaneous locomotor and exploratory behaviour, symptoms that are highly similar to those observed in human Parkinson's spectrum disorders. Analysis of the major intrinsically disordered NOTCH2-associated receptor 2 knockout mice brain revealed significant anomalies in neuronal function and appearance including the loss of tyrosine hydroxylase-positive neurons in the pars compacta, which was accompanied by an up-regulation in α-synuclein protein expression. Taken together, these data demonstrate a previously unknown function for major intrinsically disordered NOTCH2-associated receptor 2 in the pathogenesis of Parkinson's spectrum disorders. Abstract : Major intrinsically disordered NOTCH2-associated receptor 2 is a novel endoplasmic reticulum protein expressed in brain neuronal and glial cells, and its expression is down-regulated in patients with Lewy body dementia. Loss of major intrinsically disordered NOTCH2-associated receptor 2 in mouse results in motor deficits such as rigidity and bradykinesia, gait abnormalities, reduced spontaneous locomotor and exploratory behaviour. Graphical Abstract: